EFFECTS OF STRATIGIC MARKETING ON BUSINESS PERFORMANCE OF SMALL BUSINESS IN BAKARA MARKET MOGADISHU SOMALIA - MOHAMUD, ALI YUSUF; gichinga, Dr Lucy (IJRDO - Journal of Business Management, 2016)
The purpose was to investigate the impact of small businesses on the Marketing strategy on business Performance in Mogadishu -Somalia, by identifying and understanding the best ways that small businesses can be successful. and to find out the role of small business in marketing strategy on business Performance The general objective of the study is to investigate the effects of strategic marketing on business performance the research question of this study was what assess the effects of market Segmentation on Business Performance How To assess the effects of Cost Leadership on Business Performance .The Research Design a descriptive case study approach was use in order to determine and report about the effects of strategic marketing on business performance of small business. The sample technique of this study was simple random sampling. The questionnaire translates the research objective into specific questions target population of small business of Mogadishu Somalia. The questionnaire was 75 employees. Proportionate stratified random sampling technique was used for this study. The data collected in this study was analyzed using descriptive statistics through SPSS version 16.0. There was a weak positive but insignificant business Performance correlation market segmentation There was a weak positive and significant business Performance correlation between cost leadership There was a strong negative and highly significant correlation between product differentiation and business performance There was a moderately positive and highly significant correlation between effects of market strategy and business performance .